Neutrophil extracellular traps induce aggregation of washed human platelets independently of extracellular DNA and histones - Elaskalani, O.; Abdol Razak, N.; Metharom, Pat (2018)
© 2018 The Author(s). Background: The release of neutrophil extracellular traps (NETs), a mesh of DNA, histones and neutrophil proteases from neutrophils, was first demonstrated as a host defence against pathogens. Recently it became clear that NETs are also released in pathological conditions. NETs released in the blood can activate thrombosis and initiate a cascade of platelet responses. However, it is not well understood if these responses are mediated through direct or indirect interactions. We investigated whether cell-free NETs can induce aggregation of washed human platelets in vitro and the contribution of NET-derived extracellular DNA and histones to platelet activation response. Methods: Isolated human neutrophils were stimulated with PMA to produce robust and consistent NETs. Cell-free NETs were isolated and characterised by examining DNA-histone complexes and quantification of neutrophil elastase with ELISA. NETs were incubated with washed human platelets to assess several platelet activation responses. Using pharmacological inhibitors, we explored the role of different NET components, as well as main platelet receptors, and downstream signalling pathways involved in NET-induced platelet aggregation. Results: Cell-free NETs directly induced dose-dependent platelet aggregation, dense granule secretion and procoagulant phosphatidyl serine exposure on platelets. Surprisingly, we found that inhibition of NET-derived DNA and histones did not affect NET-induced platelet aggregation or activation. We further identified the molecular pathways involved in NET-activated platelets. The most potent single modulator of NET-induced platelet responses included NET-bound cathepsin G, platelet Syk kinase, and P2Y12and aIIbß3 receptors. Conclusions: In vitro-generated NETs can directly induce marked aggregation of washed human platelets. Pre-treatment of NETs with DNase or heparin did not reduce NET-induced activation or aggregation of human washed platelets. We further identified the molecular pathways activated in platelets in response to NETs. Taken together, we conclude that targeting certain platelet activation pathways, rather than the NET scaffold, has a more profound reduction on NET-induced platelet aggregation.